THE THE INFLUENCE OF INTERNAL AND EXTERNAL VARIABLES ON THE WORLD ETHEREUM PRICE: COINTEGRATION ANALYSIS (JEB17 : Jurnal Ekonomi dan Bisnis, 2024)
This study aims to analyze the impact of internal variables, including total Ethereum, number of transactions, fees per transaction, and number of active wallets, as well as external variables, namely the price of Bitcoin and the price of gold, on global Ethereum prices. The study utilizes daily data covering the period from December 31, 2016, to December 31, 2021. The data analysis employs time series data with the assistance of Eviews 10 and the error correction model (ECM) method. The study's findings indicate that total Ethereum, number of transactions, fees per transaction, number of active wallets, price of Bitcoin, and price of gold collectively exert a significant influence on Ethereum prices. However, when examined individually, total Ethereum demonstrates a negative impact and lacks statistical significance on Ethereum prices. Similarly, the number of transactions exhibits a negative and significant effect on Ethereum prices. Conversely, transaction fees, number of active wallets, and the price of Bitcoin have a positive and significant impact on Ethereum prices. Meanwhile, global gold prices do not exhibit any influence on Ethereum prices.